The impact of financial development and institutional quality on environmental quality in the Western Balkans (European Journal of Government and Economics, 2026)
Using a panel dataset of six Western Balkan countries for the period 2010–2022, this study employs dynamic econometric models such as Fixed Effects (FE), Random Effects (RE), Generalized Method of Moments (GMM), and the Two-Stage Least Squares (2SLS) to examine the impact of financial development and institutional quality on environmental quality. The determinants of environmental quality considered in the analysis include economic growth, foreign direct investment, trade openness, and institutional quality. Institutional quality is measured as the average of political stability, regulatory quality, and corruption index.Financial development is proxied by domestic credit to private sector. The findings indicate that both domestic credit to private sector and institutional quality have a significant positive impact on CO₂ emissions. This suggests that an increase in credit to the private sector leads to a significant increase in carbon emissions. Similarly, improved institutional quality is associated with increased emissions, a result that can be explained by the fact that countries with stronger institutions tend to attract investment and develop infrastructure, which can lead to higher economic activity, energy consumption and pollution. These results highlight the need for balanced policy approaches that support financial development and institutional improvement while also promoting environmental sustainability. The study offers valuable insights for policymakers in the Western Balkans to design integrated strategies that align financial and institutional progress with environmental protection goals.